1958
DOI: 10.1161/01.cir.17.4.653
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Renin as Proof of the Pathogenesis of Sustained Renal Hypertension

Abstract: Antirenin to hog renin produced in the dog neutralizes the acute pressor effect of dog as well as hog renin. A course of intramuscular injections of hog renin in chronic renal hypertensive dogs produces an antihypertensive effect which is correlated with the antirenin titers of the plasma. Passive transfer of high titer homologous antiserum to hog renin produces an antihypertensive effect in chronic renal hypertensive dogs which is correlated with the antirenin titer. The results suggest a pathogenetic role fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Several investigators have actively or passively immunized Goldblatt hypertensive rabbits (9, 10), dogs (27,28), or rats (29-31) against angiotensin II or renin. The interpretation of all these results is somewhat difficult because various techniques and hypertensive models have been used, and very often important information such as antibody titers achieved in vitro or in vivo is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have actively or passively immunized Goldblatt hypertensive rabbits (9, 10), dogs (27,28), or rats (29-31) against angiotensin II or renin. The interpretation of all these results is somewhat difficult because various techniques and hypertensive models have been used, and very often important information such as antibody titers achieved in vitro or in vivo is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Proof of principle was established first by use of immunization against renin, 14 followed by studies with a nonspecific inhibitor, pepstatin, and finally with peptide mimics of either prorenin or of the renin substrate angiotensinogen. 15,16 Several of the peptide mimics were developed as possible drugs, and the invaluable knowledge gained has already been well described in the review of renin inhibitors by Staessen et al 17 Parenteral administration of peptide inhibitors to salt-depleted subjects confirmed proof of principle as an effective mechanism of blood pressure reduction, 18 and the development of tetrapeptides led to clinical investigation of orally administered compounds (enalkiren, remikiren, zankiren).…”
Section: The Target For Direct Renin Inhibitionmentioning
confidence: 99%
“…In studies with anti-renin, passive transfer of dog anti-renin serum produced an antihypertensive effect in the renal hypertensive dog (Wakerlin, 1958). In the rat, dog anti-renin serum inhibited the pressor response to renin, but did not reduce the blood pressure of renal hypertensive rats (Weiser & Hoobler, 1964).…”
Section: Discussionmentioning
confidence: 99%